Brokering Mergers: An Agency Theory Perspective on the Role of Representatives - Kesner, Idalene F.; Shapiro, Debra L.; Sharma, Anurag (Academy of Management Journal, 1994)
Agency theory suggests a conflict of interest in the relationship between investment bankers and the firms they represent during merger negotiations. We examined this proposition by scrutinizing the association between the compensation bankers earned and the premiums paid in mergers. Results show a positive relationship between premium and compensation for investment bankers of both target and bidder firms. This relationship indicates alignment between the goals of the targets and their representatives but suggests misalignment, and hence conflict of interest, in the case of bidders.